1987
DOI: 10.1128/jvi.61.10.3102-3108.1987
|View full text |Cite
|
Sign up to set email alerts
|

CD8-positive T lymphocytes specific for murine cytomegalovirus immediate-early antigens mediate protective immunity

Abstract: We have shown in a murine model system for acute, lethal cytomegalovirus (CMV) disease in the immunocompromised natural host that control of virus multiplication in tissues, protection from virus-caused tissue destruction, and survival are mediated by virus-specific CD8+ CD4-T lymphocytes. Protection from a lethal course of disease did not result in a rapid establishment of virus latency, but led to a long-lasting, persistent state of infection. The CD8-CD4+ subset of T lymphocytes was not effective by itself … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
154
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(159 citation statements)
references
References 37 publications
5
154
0
Order By: Relevance
“…Infection spreads to astrocytes within the brain parenchyma only in the absence of an effective CD8 + T cell response [10]. Reports by other groups have also established the importance of CD8 + T cells for control of primary infection [11,12]. Likewise, previous studies from our laboratory have shown that antigen-specific CD8 + T cells persist within the brain even in the absence of detectable viral protein [13].…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Infection spreads to astrocytes within the brain parenchyma only in the absence of an effective CD8 + T cell response [10]. Reports by other groups have also established the importance of CD8 + T cells for control of primary infection [11,12]. Likewise, previous studies from our laboratory have shown that antigen-specific CD8 + T cells persist within the brain even in the absence of detectable viral protein [13].…”
Section: Introductionmentioning
confidence: 56%
“…Cells of the B-lineage enter the CNS in response to acute viral infection, and like T cells, they are retained within the brain into the chronic phase. Although CD8 + T cells play a critical role in controlling viral spread during acute brain infection [10,11], prolonged immune responses within the brain following MCMV infection are characterized by persistence of Abproducing B cells, chronic microglial cell activation, and retention of virus-specific memory CD8 + T cells [7,13]. Like other herpesviruses, MCMV establishes latency after control of acute infection and clearance of detectable viral antigen.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged immune responses within the brain following MCMV infection are characterized by persistence of antibody-producing B-cells, chronic microglial cell activation, and retention of MCMV-specific effector-memory CD8 1 T-cells (Mutnal et al, 2011b;Mutnal et al, 2012). Although CD8 1 T-cells play an important role in controlling acute brain infection (Reddehase et al, 1987(Reddehase et al, , 1985, the chronic presence of these IFN-g-producing T-cells may be damaging to the brain. Although retention of antigen-specific CD8 1 T-cells following MCMV infection helps to protect against virus reactivation, they are also responsible for long-term activation of microglia throughout the brain (Mutnal et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
“…Recognition of nonstructural viral proteins by the human immune system that raise an effective immune response and mediate protective immunity has been reported in several viral systems (39,40). We describe for the first time PBMC that specifically recognize HBxAg, a nonstructural protein of HBV.…”
Section: Discussionmentioning
confidence: 92%